Theoretic analysis and experimental evaluation of the spectrum transmission coefficient of a multilayer photovoltaic vacuum glazing. (15th September 2020) - Lv, Qinghua; Cui, Jiachen; Jarimi, Hasila; Lv, Hui; Zhai, Zhongsheng; Su, Yuehong; Riffat, Saffa; Dong, Shijie
Abstract: This paper introduces an innovative thin film PV vacuum glazing (PV-VG) technology. In addition to electricity generation, the PV-VG glazing can also reduce heat loss from the building in winter and reduce heat gain in summer. In building integrated photovoltaics application, optical characterization of the PV glazing is important in determining the solar ray transmission and thermal transfer process of the glazing. This paper discusses the optical properties of the PV-VG glazing by considering the different layers of the glazing unit that includes a self-cleaning glass, a thin film PV glass and a low-e vacuum glazing. Based on the optical transfer matrix, the transmission coefficients of different film layers were deduced. The theoretical calculations were then validated against the transmission coefficient experiment of the PV-VG using an EDTM SS2450 Solar Spectrum Meter. The calculation error of the transmission coefficient of the single-layer glazing is generally within 5%, the calculation error of the transmission coefficient of the integrated PV-VG glazing is about 6%. The results show that the average visible light transmission coefficient, the average infrared light transmission coefficient and the overall transmission coefficient of PV-VG glazing are 19%, 16% and 12%, respectively. The study is important to optimize the visible light transmission of the PV-VG glazing; the optical model obtained above lays a solid foundation for further study of transmission coefficient analysis of different functional coating of PV-VG glazing.